The definition of neutrophil extracellular traps and the concentration of short-chain fatty acids in salmonella-induced inflammation of the intestine against the background of vancomycin and Bacteroides fragilis - Yu. V. Bukina; B. О. Varynskyi; A. V. Voitovich; G. D. Koval; A. G. Kaplaushenko; А. M. Kamyshnyі (Patologìâ)
Abstract